Mechanistic Insights Into Filamentous Phage Integration In Vibrio cholerae - Das, Bhabatosh (Frontiers in Microbiology, 2014)
Vibrio cholerae, the etiological agent of acute diarrhoeal disease cholera, harbors large numbers of lysogenic filamentous phages, contribute significantly to the host pathogenesis and provide fitness factors to the pathogen that help the bacterium to survive in natural environment. Most of the vibriophage genomes are not equipped with integrase and thus exploit two host-encoded tyrosine recombinases, XerC and XerD, for lysogenic conversion. Integration is site-specific and it occurs at dimer resolution site (dif) of either one or both chromosomes of V. cholerae. Each dif sequence contains two recombinase-binding sequences flanking a central region. The integration follows a sequential strand exchanges between dif and attP sites within a DNA-protein complex consisting of one pair of each recombinase and two DNA fragments. During entire process of recombination, both the DNA components and recombinases of the synaptic complex keep transiently interconnected. Within the context of synaptic complex, both of the actuated enzymes mediate cleavage of phosphodiester bonds. First cleavage generates a phosphotyrosyl-linked recombinase-DNA complex at the recombinase binding sequence and free 5’-hydroxyl end at the first base of the central region. Following the cleavage, the exposed bases with 5’-hydroxyl ends of the central region of dif and attP sites melt from their complementary strands and react with the recombinase-DNA phosphotyrosyl linkage of their recombining partner. Subsequent ligation between dif and attP strands requires complementary base pair interactions at the site of phosphodiester bond formation. Integration mechanism is mostly influenced by the compatibility of dif and attP sequences. dif sites are highly conserved across bacterial phyla. Different phage genomes have different attP sequences; therefore they rely on different mechanisms for integration. Here, I review our current understanding of integration mechanisms used by the vibriophages.